Decrease in serum levels of autotaxin in COVID-19 patients. (31st December 2022) - Shimura, Takuya; Kurano, Makoto; Okamoto, Koh; Jubishi, Daisuke; Hashimoto, Hideki; Kano, Kuniyuki; Igarashi, Koji; Shimamoto, Satoshi; Aoki, Junken; Moriya, Kyoji; Yatomi, Yutaka
Abstract: Introduction: In order to identify therapeutic targets in Coronavirus disease 2019 (COVID-19), it is important to identify molecules involved in the biological responses that are modulated in COVID-19. Lysophosphatidic acids (LPAs) are involved in the pulmonary inflammation and fibrosis are one of the candidate molecules. The aim of this study was to evaluate the association between the serum levels of autotaxin (ATX), which are enzymes involved in the synthesis of lysophosphatidic acids. Material and methods: We enrolled 134 subjects with COVID-19 and 58 normal healthy subjects for the study. We measured serum ATX levels longitudinally in COVID-19 patients and investigated the time course and the association with severity and clinical parameters. Results: The serum ATX levels were reduced in all patients with COVID-19, irrespective of the disease severity, and were negatively associated with the serum CRP, D-dimer, and anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody levels. Discussion: Considering the biological properties of LPAs in the pulmonary inflammation and fibrosis, modulation of ATX might be compensatory biological responses to suppress immunological overreaction especially in the lung, which is an important underlying mechanism for the mortality of the disease. Conclusions: COVID-19 patients showed a decrease in the serum levels of ATX, irrespective of the disease severity. Key Messages: Autotaxin (ATX) is an enzyme involved in the synthesis of lysophosphatidic acid (LPA), which has been reported to be involved in pulmonary inflammation and fibrosis. Patients with COVID-19 show decrease in the serum levels of ATX. Modulation of ATX might be compensatory biological responses to suppress immunological overreaction.